Persepsi Mahasiswa Terhadap Leksikon Wisata Kuliner Khas Madura - Pramitha Devi Normalia; Siti Hanifa (Journal of Social, Culture, and Language, 2022)
Typical food is a factor that is used by a region as an attraction to attract tourists. Culinary in an area is certainly different from the other areas. Madura is an island located in East Java Province. In this study aims to determine student perceptions of culinary from Madura. This study used a descriptive qualitative method to describe students' perceptions the names of foods that have been determined. In this study, it was found that 52% of students knew about Madurese culinary and some of them often consumed. While 48% of students did not know the food in question because they came from another area of Madura. Some of the food was mentioned as coming from 2 regions by correspondents. This triggers different perceptions of each individual student. Keywords: Perceptions, Student, Culinary, Madura